Pengujian dan Analisis Teknik Steganografi Menggunakan Metode Playfair, ElGamal, dan LSB untuk Penyembunyian Data pada Gambar Digital dalam Aplikasi Modern - Pardosi, Sion Saut Parulian; Manik, Melvayana; Situmorang, Irene Mutiara (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2024)
The rapid advancement of information and communication technology has significantly transformed how individuals interact and share information, particularly through digital media such as images. While offering numerous benefits, the ease of digital media manipulation poses serious challenges, including cybercrimes like phishing and cyberbullying, highlighting the need for reliable data protection methods to maintain information confidentiality. This research focuses on steganography, the art of concealing messages in such a way that only the sender and recipient are aware of the hidden information. The study implements the Least Significant Bit (LSB) technique for embedding secret files within digital images and evaluates its effectiveness across various transmission scenarios, including email and instant messaging applications like WhatsApp, Instagram, and Telegram. Additionally, the research incorporates cryptographic algorithms such as Playfair and ElGamal to enhance data security. The findings aim to provide insights into the strengths and weaknesses of these methodologies, ultimately contributing to the development of secure digital communication practices.